Satisfacción de los beneficiarios con la Cooperación Universitaria al desarrollo de la seguridad del paciente en el marco del proyecto Soludable Ecuador. - Moya Amaguaya, Valeria Del Rocío (2024)
The University Cooperation, as a contribution of the Center for Development Initiatives of the University of Granada, promotes a set of actions directed by the educational community for the benefit of the most disadvantaged countries, promoting peace, equity, and human development through international funding of projects that contribute to the solution of problems of society through research and innovation. The University has developed the project " Healthy Badge Ecuador: Certification of the Healthy Distinctive on Photoprotection and Cancer Prevention, and Strengthening of the Strategic Line of Patient Safety in the Faculty of Health Sciences of Riobamba" to promote photoprotection measures for the prevention of skin cancer being necessary to determine the satisfaction of the beneficiaries on the policies implemented under this project, It is essential to conduct descriptive, observational, quantitative and cross-sectional research, using as data collection technique an online questionnaire of Microsoft forms, applied to 782 participants among students, teachers, administrative and service staff of the nursing and medicine careers of the Faculty of Health Sciences of the National University of Chimborazo (UNACH). The results showed that most of the university community is aware of the risk of overexposure to the sun, adopting models of healthy behavior that prevent skin cancer. In addition, the promotion of photoprotection practices to avoid exposure to UV rays and the increase of natural and artificial shade spaces allowed the accreditation of the Faculty of Health Sciences with the healthy badge granted by the Hospital Universitario Costa de Sol, which belongs to the council meeting in Andalucía-Spain. It is concluded that the participants are satisfied with the photoprotection policies implemented: use of safe external protection, outdoor activities in shaded areas and at non-risk times, personal photoprotection, and continuous training. In this sense, the healthy badge Ecuador project has contributed to improving the university community's health and quality of life. It is recommended that photoprotection policies be implemented in other UNACH faculties, emphasizing the importance of the audience's involvement in this process. The training program should be extended to different national and international universities, and follow-up studies should be carried out to evaluate the project's sustainability.